2016
DOI: 10.5603/fm.a2015.0077
|View full text |Cite
|
Sign up to set email alerts
|

Symmetrical anatomical variant of the anterior belly of the digastric muscle: clinical implicat

Abstract: (Folia Morphol 2016; 75, 1: 112-116)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…The submental arrowhead variation of the anterior digastric and mylohyoid musculature-Review of the literature reveals numerous case studies that have reported a muscular variant connecting the midline raphé of the mylohyoid to the intermediate tendon of the digastric muscle [4,5,16,26,27,[32][33][34]. Williston describes a case wherein "[t]he tendon of the digastric muscles gave off two anterior bellies, one normal in size and position, the other a flattened, triangular belly, meeting its fellow in a median raphe and connected at its upper angle with the maxillary symphysis" [32].…”
Section: The Mylohyoid Musclementioning
confidence: 99%
See 1 more Smart Citation
“…The submental arrowhead variation of the anterior digastric and mylohyoid musculature-Review of the literature reveals numerous case studies that have reported a muscular variant connecting the midline raphé of the mylohyoid to the intermediate tendon of the digastric muscle [4,5,16,26,27,[32][33][34]. Williston describes a case wherein "[t]he tendon of the digastric muscles gave off two anterior bellies, one normal in size and position, the other a flattened, triangular belly, meeting its fellow in a median raphe and connected at its upper angle with the maxillary symphysis" [32].…”
Section: The Mylohyoid Musclementioning
confidence: 99%
“…Williston describes a case wherein "[t]he tendon of the digastric muscles gave off two anterior bellies, one normal in size and position, the other a flattened, triangular belly, meeting its fellow in a median raphe and connected at its upper angle with the maxillary symphysis" [32]. Other accounts are largely similar to that of Williston [4,5,16,26,27,33,34]. Buck and Stedman note that "[t]he anterior belly is very often abnormal; not infrequently the two anterior bellies unite in the median line and completely shut out from view the mylohyoid muscles" [4].…”
Section: The Mylohyoid Musclementioning
confidence: 99%
“…The closest variation to these atavistic variations we could find in the literature was a variation in which right and left AB accessory muscles fused at the midline of the submental triangle. In this case, the ABDMs and the accessory muscles were still visibly discernable by distinct striations of the muscle fibers [1]. Another is the complex type variation with an ectopic tubercle elongated from the mandible at the symphysis, to which a pair of insertion type AB accessory muscles are attached via a tendinous fiber (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Clinically, structural variations of the ABDM have implications in surgeries involving the muscles of the submental region such as correction of facial paralysis and an array of cosmetic surgeries for improving the frontal neck contour [5,9,10,23,26]. The ABDM variations, especially those with atavistic type variation and robust AB accessory muscles, could cause misidentification of the suprahyoid muscle groups which affects diagnosis involving the submandibular region [1,26,27]. Therefore, attracting attention to the frequent occurrence and morphological complexity of ABDM variations in the general population has significant clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…While, a deficiency during differentiation of the mesodermal cells may either result in a unilateral or bilateral accessory belly (Chaithra Rao et al). As a result, bilateral accessory bellies have been frequently documented in literature (Aktekin et al; Liquidate et al; Mascaro et al; Kyung et al; Chaithra Rao et al) and the majority of these are asymmetrical (Rani et al;Buffoli et al, 2016;Accioly Lins et al, 2017). This study documented both unilateral and bilateral accessory belly variations.…”
Section: Discussionmentioning
confidence: 99%